2008
DOI: 10.1089/jamp.2007.0651
|View full text |Cite
|
Sign up to set email alerts
|

Aerosol Deposition in the Human Lung Periphery Is Increased by Reduced-Density Gas Breathing

Abstract: Aerosol mixing resulting from turbulent flows is thought to be a major mechanism of deposition in the upper respiratory tract (URT). Because turbulence levels are a function of gas density, the use of a low-density carrier gas should reduce deposition in the URT allowing the aerosol to reach more peripheral airways of the lung. We performed aerosol bolus tests on 11 healthy subjects to investigate the effect of reduced gas density on regional aerosol deposition in the human lung. Using both air and heliox (80%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
16
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(18 citation statements)
references
References 20 publications
1
16
1
Order By: Relevance
“…Despite this effect of the inertial impaction mechanism in both cases, the deposition under air was ≥ 40% higher than He (see Table 4). This is due the reduction in turbulence and flow resistance, which is in well agreement to the similar observations reported in different prior studies (Anderson et al, 1990;Ari et al, 2011;Darquenne and Prisk, 2004;Katz et al, 2014;Miyawaki et al, 2012;Peterson et al, 2008). Matida et al, (2006) and Ilie et al, (2008) in their study of particle deposition for cases with/without turbulence modeling, reported that turbulence mechanism is as important as the impaction mechanism.…”
Section: Global Depositionsupporting
confidence: 90%
See 2 more Smart Citations
“…Despite this effect of the inertial impaction mechanism in both cases, the deposition under air was ≥ 40% higher than He (see Table 4). This is due the reduction in turbulence and flow resistance, which is in well agreement to the similar observations reported in different prior studies (Anderson et al, 1990;Ari et al, 2011;Darquenne and Prisk, 2004;Katz et al, 2014;Miyawaki et al, 2012;Peterson et al, 2008). Matida et al, (2006) and Ilie et al, (2008) in their study of particle deposition for cases with/without turbulence modeling, reported that turbulence mechanism is as important as the impaction mechanism.…”
Section: Global Depositionsupporting
confidence: 90%
“…A decreasing (increasing) gas density (kinematic viscosity) effectively minimizes the turbulence and flow resistance, which effectively reduces particle dispersion (Anderson et al, 1990;Ari et al, 2011;Darquenne and Prisk, 2004;I. Katz et al, 2014;Miyawaki et al, 2012;Peterson et al, 2008). Consequently, the particle deposition during the inspiration phase increases (decreases)…”
Section: Global Depositionmentioning
confidence: 99%
See 1 more Smart Citation
“…Owing to this unique physical property, He-O 2 mixtures may potentially be useful in the treatment of conditions such as increased upper airway resistance, asthma, and chronic obstructive pulmonary disease to decrease work of breathing and dyspnea [2][3][4]. The effects of He-O 2 mixtures can also be used for optimizing particle deposition in the human respiratory tract, but will depend on physical properties of the mixture such as density, viscosity, and mean free path [5][6][7]. The clinical efficacy of breathing an He-O 2 mixture, however, has not been firmly established [8].…”
Section: Introductionmentioning
confidence: 99%
“…Further to its potential role as a therapeutic agent on its own, He/O 2 has been advocated as a carrier gas to better transport medical aerosols into obstructed lungs (Anderson & Svartegren, 1993;Corcoran & Gamard, 2004;Kim, Saville, Sikes, & Corcoran, 2006;Kress et al, 2002;Manthous et al, 1995;Peterson, Prisk, & Darquenne, 2008). In this application, it is important to assess the effects of varying gas properties not only on the mechanics of particle deposition in the respiratory tract, but also on aerosol production processes.…”
mentioning
confidence: 99%